ANALISIS DAN EVALUASI KINERJA RUAS JALAN KH. MUKMIN DI KABUPATEN SIDOARJO DENGAN METODE MANUAL KAPASITAS JALAN INDONESIA 1997 (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2021)
Jalan KH Mukmin in Sidoarjo Regency is a secondary connecting road for the cities of Surabaya and Mojokerto and is one of the culinary centers of food, business and education all day long passing through this road section, over time many vehicles pass through this section which results in unstable flow, vehicle queues It is also exacerbated by side climbing such as the number of vehicles coming out of village alleys, parking on street and pedestrians crossing the road. This causes congestion, especially during rush hour. Problems in a KH Mukmin road section are caused by the high volume of traffic because it needs a solution to reduce traffic also to find out how to reduce the volume of traffic on the road in the research year and to know the performance of the KH Mukmin road section after the traffic volume has decreased. The data used in this study are primary data obtained from field surveys and secondary data obtained by the Transportation Agency of Sidoarjo Regency, Bappeda of Sidoarjo Regency, and the Road Transportation Safety Performance Book in Sidoarjo Regency in 2019. The primary data are road geometry data and traffic volume data. obtained by conducting a traffic volume survey for 2 days (11 and 12 November 2019). Secondary data in the form of population data, road network data and road function data. Analysis of road performance using the 1997 Indonesian Road Capacity Manual (MKJI) method with the degree of saturation (DS) as the main indicator of road segment performance. The results of the analysis show the performance of the KH. Believers according to the 1997 MKJI method are 0.86 with a level of D. To improve the performance of the KH Mukmin road in the research year, the solution is to choose the volume of motorcycle traffic to Erlangga road and after diverting the volume of motorcycle traffic to the road Erlangga, the performance of the KH Mukmin road segment increases to 0.64 with a service level of B. volume. The purpose of this study was to determine the performance of the KH. The believer is